Three-dimension Glyceraldehyde-3-Phosphate Dehydrogenase protein structure of substitution and insertion sequences of GAPDH gene of chicken drumstick meat (Gallus gallus) - Fatchiyah Fatchiyah; Rista Nikmatu Rohmah; Lidwina Faraline Tripisila; Dewi Ratih Tirto Sari; Adelia Adrianne Tapiory; Jihan Safira Ainnayah; Viona Faiqoh; Fajar Mustika Alam; Ahmad Faizal Abdul Razis (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2022)
The study aimed to observed the 3-D structure of GAPDH protein and identify the GAPDH gene sequences mutation of chicken drumstick meat (Gallus gallus). The sample of chicken meat was randomly taken in four districts in Malang city. In this study, the DNA was isolated from drumstick meat chicken samples, amplified using proper primers, and then sequenced using ABI 3730xl DNA Sequencer. The DNA sequences alignments analyzed by BioEdit software and the control sequence of GAPDH gene was obtained from NCBI GenBank (sequence Gene ID: 374193). Then, the amino acid sequence and 3D structure of GAPDH protein were determined based on the change of nucleotide sequences using Swiss model and PyMol software. The nucleotide sequence of a partially GAPDH gene of drumstick meat chicken from districts two is completely different with a 97% similarity level, which found twelve nucleotides’ substitutions mutation between nucleotide base number 354 until 777 and three nucleotides inserted between T753 and G754 nucleotide base. These mutations changed the amino acid sequence and 3D structure of GAPDH protein. This result suggests that the differential drumstick chicken meat GAPDH sequences and 3D structure may induce the change of protein-protein interaction and induction.